Challenges to Admitting Residents: Perspectives from Rural Nursing Home Administrators and Staff - Carrie Henning-Smith PhD, MPH, MSW; Dori Cross PhD; Adrita Rahman MPH (SAGE Publishing, 2021)
Rural residents are older, on average, than urban residents, with more underlying health conditions and higher rates of disability. Rural nursing homes face unique challenges admitting medically-complex patients and meeting their needs throughout their stay. These challenges may be amplified for certain health conditions. Greater geographic distances also strain transitional care coordination practices with health system referral hubs in urban areas. In this study, we assess perceptions of difficulty rural nursing homes encounter in admitting and serving individuals with dementia, obesity, mental and behavioral health conditions, and medically complex conditions. Using a survey of nursing home administrators located in non-metropolitan counties across the U.S. (n = 209), we assessed the self-reported degree of difficulty identified in serving each of the 4 type of conditions, coupled with qualitative analysis of open-ended questions identifying specific challenges. Rural nursing homes have capacity constraints owing to lower population density, limited financial resources, and unique challenges recruiting and retaining workforce to rural areas. Nursing home administrators reported the most challenges to providing high-quality care to residents with mental and behavioral health challenges, followed by obesity. For specific challenges, administrators focused primarily on staffing concerns, as well as space and equipment needs. Rural nursing home administrators identified challenges related to specific conditions and capacity constraints. To ensure appropriate and high-quality nursing home placement for rural residents, and to minimize the disruption of transitions into nursing home settings, more attention is needed on addressing the constraints identified by rural nursing home administrators in this study.